(3TQM Ydi dGejI GHf GdMGLH aj GdYQhVs - (3MSf Hf bGSe GdoeQGOj GdeGdcjs; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG JYdjbi GdEeGe CHj YeQh Hf GdMGLH s
(3BNQgG (B:s
(3hgh GdSGcf GdPj jbHd GdMQcI cCda YUi hGdMeO ddg QH GdYGdejf s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 24) s
Keywords: (3GdYQhV hGdbhGais